The impact of healthcare expenditure and healthcare sector growth on Co2 emission using dynamic panel data system GMM estimation model during COVID 19 crisis - Intan Maizura, Abd Rashid; Wan Ahmad Fauzi, Wan Husain; Irza Hanie, Abu Samah; Hariri, Hamzah; Mohammad Harith, Amlus; Elsayed, Elsiefy; Amirah Hazimah, Borhanordin; Harniyati, Hussin (AIP Publishing, 2023)
The striking global transmission of COVID-19 has empowered numerous governments to intervene in order to keep the contamination at bay. Medical tourism could be a developing marvel with arrangement ideas for wellbeing frameworks, particularly in goal countries. Medical tourism, a rapidly growing industry, has been identified as a potential source of financial diversification by a number of countries. This study proves that government expenditure is significantly affected by CO2 emission and sectors, all in contributions to pollution. Despite the fact that Indonesia is one of the most popular destinations for therapeutic tourism, research into its competitiveness has been limited and limited in scope. This case study employs a quantitative approach to identify and analyse the variables that position Indonesia as a viable medical tourism destination. Based on an all-inclusive approach, this investigation discovered that coordinating various procedures for restorative tourism advancement with sound government arrangements and proactive administration practises has resulted in significant positive results toward shared victory of Indonesia’s tourism and healthcare segments.